FR1.2: Is Women's Empowerment Bearing Fruit? Mapping Women's Empowerment in Agriculture Index (WEAI) results to the Gender and Food Systems Framework - Myers, Emily; Heckert, Jessica; Faas, Simone; Malapit, Hazel J.; Meinzen-Dick, Ruth S.; Raghunathan, Kalyani; Quisumbing, Agnes R. (International Food Policy Research Institute, 2022)
This review examines the relationships between domains of women's empowerment and food system outcomes, as defined by the Gender and Food Systems Framework (Njuki et al. 2022). We reviewed papers that cited both the original WEAI and/or pro-WEAI papers, Alkire et al., (2013) and Malapit et al. (2019), between 2013 and April 2022. The literature search had the following additional inclusion criteria: published in English; published as a journal article or working paper; calculated a WEAI, A-WEAI, or pro-WEAI metric and/or indicator; and, reported significance level of a food system outcome. We found that women's empowerment is significantly associated with various outcomes, though which aspect of empowerment matters for a particular outcome varies across contexts. Many studies found significant positive associations between women's empowerment and intrahousehold gender equality with various children's dietary and nutrition outcomes; household food security; and agricultural production indicators. Several studies document significant associations between empowerment indicators and women's dietary diversity scores, but with mixed results. The findings suggest that increasing women's empowerment and closing empowerment gaps contribute to improved dietary and nutrition outcomes, but household wealth, gender norms, and country-specific institutions are also critical. Most papers identified illustrate associative relationships; future research may investigate these relationships more deeply to determine causal relationships that drive desired food system outcomes. Further, stronger commitments to address structural and institutional barriers to gender equality in policy may enhance food system outcomes.